ANALISIS LAJU PERTUMBUHAN, EFEKTIVITAS DAN KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA MALANG - Maha Putra, Gusti Ngurah Rai (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
As Malang city thrives into one of major tourism destinations in East Java, the number of its visitorsrises significantly and the amount of restaurants, as well as the city’s income from the restaurant tax, increases. This study is aimed at determining the extent to which the growth rate and effectiveness of the income gained from the restaurant tax contribute to the city’s local own-source revenue. The result of the study reveals that the average growth rate is 20%, which is categorized as unsuccessful; the average effectiveness of the restaurant tax income, however, reaches 111%, which signifies very good. The other research outcome shows that the average contribution of the restaurant tax to the city’s own-source revenue is very low as amounted 9%. Dinas Pendapatan Daerah (Regional Office of Local Revenue) should formulate more strategic efforts to explore the restaurant tax potentials, such as through intensification and extension of the growth rate, effectiveness, and contribution of the city’s restaurant tax. Keywords: Restaurant tax; Growth rate; Effectiveness; Contribution; Local own-source revenue, Dinas Pendapatan Daerah (Regional Office of Local Revenue)